Three/Four-leg Inverter Current Control Based on Generalized Symmetrical Components - Liberado, E. V. [UNESP]; Pomilio, J. A.; Alonso, A. M.S. [UNESP]; Tedeschi, E.; Marafão, F. P. [UNESP]; Guerreiro, J. F. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Considering a scenario of high penetration of voltage source inverters in distribution grids, on which the number of conductors is variable, this paper proposes a current control approach for three- or four-leg inverters based on the generalized symmetrical components decomposition of non-sinusoidal signals. The approach is an alternative to d-q and α-β transformation-based approaches and allows to model and design the control system directly in the abc frame. Simulation results of three- and four-leg inverters operating as multifunctional interfaces of distributed energy resources are presented, as well as comparative results of the proposed approach and other abc frame-based approaches to control four-leg inverters.
Keywords: control of power converters; distributed energy resources; generalized symmetrical components; multifunctional power converter; switching power interface